Ascending testis following inguinal hernia repair in children - Abes, M.; Bakal, U.; Petik, B. (Verduci Publisher, 2015)
OBJECTIVE: Failure to replace the testes in the scrotum during hernia repair leads to iatrogenic undescended testes. At other times, the testes may spontaneously move back to the inguinal area after being placed in the scrotum, thus resulting in ascending testes. The cases in this study were assessed. PATIENTS AND METHODS: Records of 910 boys operated due to inguinal hernia were assessed retrospectively. Following hernia repair, the testes were placed in the scrotum. After the operation, all the testes were checked for being in the scrotum. They were called for follow-up after the operation. Their testes were checked for remaining in the scrotum. RESULTS: Ascending testes were detected in 4 (0.43%) of the patients. These patients had scrotal hypoplasia and/or retractile testes. Their age ranged between 1-3 years. Ascending testes were bilateral in 2 patients, and on the right side in 2. Human chorionic gonodotropin (hCG) was initiated in 3 patients. Two of them improved. Two underwent scrotal orchiopexy. CONCLUSIONS: These patients may benefit from hCG in the early postoperative period. Later, scrotal orchiopexy may be needed. Patients who have retractile testes or scrotal hypoplasia in addition to inguinal hernia need orchiopexy together with herniorrhaphy.
Keywords: Inguinal hernia; Herniorrhaphy; Ascending testis; hCG; Scrotal orchiopexy